The dead ringer : a novel - Bahr, Dane (Counterpoint, 2026)
"Montana, 1935. Bludgeoned and buried alive by his bank-robbing partner and half brother, Benjamin Kilt should have been a corpse. But now very much on this side of heaven, Kilt's quest for revenge will be unlike anything the West has ever seen. Kilt is joined on his journey by Bonnie, a thirteen-year-old Indigenous girl he somewhat reluctantly rescues from her abusive "keeper." It is through Bonnie's recollections in old age of Kilt's thorny quest for justice that Dane Bahr's masterful tale unwinds, showcasing the tragic, complicated history of the two brothers and leading to a showdown at the very ranch where they were raised"-- Provided by publisher.